Magnetostratigraphy of the fossil bearing Igbek section of the Miocene Sinap Formation, Turkey - Feseha, Mulugeta Yebyo (1996)
Absolute dating of fossil-bearing sedimentary sequences has long been of great interest to paleontologists because of the importance that absolute ages play in reconstructing phylogeny. The Igbek section in Central Turkey contains one of the richest fossil sites in the Sinap Formation. It is located about 40km east-northeast of Ankara. The sediments were deposited in a fluvial environment and range in grain size from siltstones to cobbly gravels. Paleomagnetic studies were undertaken in an attempt to date the fossil locality and correlate this site with others in the region. A total of 216 rock samples from 71 levels were collected from 92.2 m thick stratigraphic section. Most of the samples were collected from the siltstone and fine to medium-grained sandstone lithologies. Petrographic studies under normal transmitted light show that the majority of the grains are of volcanic origin with minor occurrences of metamorphic source quartz and muscovite grains. The source of the sediments is the surrounding volcanic rocks and they did not undergo much reworking. Petrographic studies under reflected light and studies of the isothermal remanent magnetization behavior of the collected samples demonstrate that magnetite is the dominant magnetic mineral, with variable but generally minor contributions of hematite. The occurrence of volcanogenic magnetite as the dominant magnetic phase indicates that the sediments carry a primary detrital remanent magnetization. Thermal and alternating field demagnetization techniques were used to isolate the characteristic magnetic vector in each of the samples. The direction of the characteristic remanent magnetic vector was calculated by the method of principal component analysis (PCA). Fisher statistics were used to calculate the declination, inclination, and virtual geomagnetic pole (VGP) for every sample and each site, and these results were in turn used to construct the magnetic reversal stratigraphy of the section. The age of the Sinap Formation is constrained by two ages, a K/Ar age of 15.2 ± 0.3 Ma for a basalt near the base of the Formation, and the datum of Hipparion, a distinctive three-toed horse that immigrated into the Old World at 10.7 Ma that is found in the Igbek fossil locality. Using these constraints, the reversal stratigraphy was correlated with the global Geomagnetic Reversal Time Scale of Cande and Kent (1995). Two alternative correlations are possible. The preferred correlation provides an age for the fossils of the Igbek section between 8.3 to 7.2 Ma. Geological Sciences